Neuro-ophthalmic manifestations of central nervous system tuberculosis: Compilation of three diverse unique presentations - Harsha Sammer Pagad (Kerala Journal of Ophthalmology, 2022)
Tubercular meningitis is the most devastating form of tuberculosis. Neuro-ophthalmic involvement can manifest as cranial nerve palsies, pupil abnormalities, disc changes, like papillitis, papilloedema, or optic atrophy and choroidal tubercles. The rate and extent of recovery are strongly. Related to early diagnosis and treatment. Herein, we describe a constellation of three cases of central nervous system tuberculosis with aberrant regeneration of oculomotor nerve, optochiasmatic arachnoiditis presenting as bilateral primary optic atrophy and the last case of parietal lobe tuberculoma presenting as homonymous hemianopia, each one with its own characteristic ocular findings.